Performance analysis of vacuum forming machines for the plastic material acryolonitrile butadiene styrene (abs) - Dede Ardi Rajab; Irwan Suriaman; Nugraha, Aji Nugraha (Jurnal Teknologika, 2024)
Plastic is a polymer material (usually an organic material) that has a high molecular weight in solid form which, when heated slowly, becomes soft and can be shaped an shaped as desired. The aim of this research is to build a vacuum forming machine. This will enable us to package a variety of products used in the home and factory industries and design a vacuum forming machine to meet the needs of the household industry. The operating principle of thermoforming and vacuum forming is used by most small and medium business for various types of product packaging. Thermoforming is a forming process where the properties of plastic fil change to become soft and flexible after going through a heating process and then using preassure or suction which adjust the shape of the mold. The vacuum forming machine consists of 3x3 hollow iron, angle iron, pallet board, 1inch iron pipe, and 2inch iron pipe. The result of the manufacture of this vacuum forming machine include several temperature stages using acryolonitrile butadiene styrene (abs) plastic material 1.5mm, square wood is used for the mold, with a heating temprature of 60-90℃, Maximum test result were obtained at a temperature of 90°C with a vacuum time 120 second.